Citrus mites in Italy. III The Acaridida (Acaridae Ewing & Nesbitt, Hemisarcoptidae Oudemans, Saproglyphidae Oudemans and Glycyphagidae Berlese) (Bollettino di zoologia agraria e bachicoltura, 2024)
The author presents the III contribution on citrus mites in Italy, referring it to the suborder Acaridida with the families Acaridae Ewing & Nesbitt, Hemisarcoptidae Oudemans, Saproglyphidae Oudemans and Glycyphagidae Berlese. Tue fundamental morphologic aspects and the relative biology notes for each group are reported. Within the family Acaridae the new subspecies Thyreophagus entomophagus italicus is described.
Keywords: Hemisarcoptidae; Acaridae; Saproglyphidae; Glycyphagidae